Is your budget your guide? The willingness to pay for a more sustainable experience in Jericoacoara - Oliveira, Laís Vieira Castro; Romero, Cláudia Buhamra Abreu; Silva, Clayton Robson Moreira da; Fontenele, Raimundo Eduardo Silveira (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This study seeks to evaluate the willingness of tourists to pay for a more sustainable experience in Jericoacoara, Ceará in Brazil. It consists of a survey of 386 tourists. The data was collected from an online questionnaire administered on location. We used the Contingent Valuation Method (CVM), a descriptive method of analysis, and multiple linear regressions. The results indicate that, on average, tourists are willing to pay R$8,51 in addition to the Sustainable Tourism Fee charged by the Municipality of Jijoca de Jericoacoara (28.4% more). We identified that the variables age, income and dependents influenced their Willingness to Pay (WTP).